The influence of HIV and smoking on mortality in patients diagnosed with tuberculosis in the state of Paraná (Research, Society and Development, 2023)
Tuberculosis (TB) is the most important opportunistic infection among people living with Human Immunodeficiency Virus (HIV). It is a risk factor for negative therapeutic outcomes in TB and increased mortality. Smoking, on the other hand, increases susceptibility to latent TB infection, progression to active disease, delayed sputum conversion, treatment non-adherence, relapse, and multidrug resistance. Additionally, when associated with HIV, smoking increases the risk of pneumonia and oropharyngeal diseases, as well as elevating the risk for cardiovascular diseases, dyslipidemia, insulin resistance, and chronic obstructive pulmonary disease. This study is a quantitative research among patients diagnosed with tuberculosis, who are HIV-positive and smokers, in the state of Paraná. The objective was to measure the impact of smoking and HIV on the mortality of patients diagnosed with tuberculosis, using the database of the Notification of Diseases Information System (SINAN), through the Department of Informatics of the Unified Health System (DATASUS) as a research instrument. At the end of the study, it was found that smoking was not a determining factor for increased mortality, while the presence of positive HIV serology significantly increased mortality rates in patients with tuberculosis.